-2z+3-z=-z-4(z+2)

Simple and best practice solution for -2z+3-z=-z-4(z+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z+3-z=-z-4(z+2) equation:


Simplifying
-2z + 3 + -1z = -1z + -4(z + 2)

Reorder the terms:
3 + -2z + -1z = -1z + -4(z + 2)

Combine like terms: -2z + -1z = -3z
3 + -3z = -1z + -4(z + 2)

Reorder the terms:
3 + -3z = -1z + -4(2 + z)
3 + -3z = -1z + (2 * -4 + z * -4)
3 + -3z = -1z + (-8 + -4z)

Reorder the terms:
3 + -3z = -8 + -1z + -4z

Combine like terms: -1z + -4z = -5z
3 + -3z = -8 + -5z

Solving
3 + -3z = -8 + -5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5z' to each side of the equation.
3 + -3z + 5z = -8 + -5z + 5z

Combine like terms: -3z + 5z = 2z
3 + 2z = -8 + -5z + 5z

Combine like terms: -5z + 5z = 0
3 + 2z = -8 + 0
3 + 2z = -8

Add '-3' to each side of the equation.
3 + -3 + 2z = -8 + -3

Combine like terms: 3 + -3 = 0
0 + 2z = -8 + -3
2z = -8 + -3

Combine like terms: -8 + -3 = -11
2z = -11

Divide each side by '2'.
z = -5.5

Simplifying
z = -5.5

See similar equations:

| -8d=96 | | 4(y-3)=.8 | | x/y-z=a | | 11+5a=1 | | 10x-10=6x+10 | | 4(.2-3x)=.8 | | y+x+40=180 | | -24+m=-11 | | 3x+13+5x-5+2x+2=180 | | 6m^2-1=-5m | | 5/9=12/n | | D=1/2kr | | p=8x+6y | | 18w-10-6=50 | | 0=12x^2+24x+24 | | -5-3(4y-2)=-1-9y | | 30=-3x-9 | | 2x+120+20=180 | | -3(x-4)+8=2 | | F=1/3n^2m | | x+(3x+3)=43 | | 5-3sin^2x-4cosx=4 | | .25(24+1)=.5(y+2) | | x+20=4x-13 | | 4-5v+5=2v-12 | | 0=3x^2-12x+6 | | 6-v=v+16 | | .25(18+1)=.5(y+2) | | 11y/15×3/5y | | 12+3x-3x= | | 24a-8-100=-2(4-7a) | | -8a-8=27-a |

Equations solver categories